Evaluating Tourists' Brand Awareness Towards Socotra Island(Yemen) Tourism Products (Journal of Namibian Studies : History Politics Culture, 2023)
A tourist’s destination brand awareness is a significant reflection of how consumers recognize a brand and involves the strength of the brand presence in the mind of consumers and the means whereby this knowledge can be easily retrieved from the mind or memory. This research study evaluates tourists’ brand awareness towards Socotra Island tourism products. This study was conducted in Socotra Island in Yemen and is exploratory in nature.  A constructed questionnaire survey of 320 international tourists provided data for descriptive and inferential analysis. The results indicate that tourists are not significantly aware of historical and cultural tourism products; however, they have shown a slight awareness of adventure tourism products. The results also showed that tourists are significantly aware of nature-based tourism products. The study suggests that the historical, cultural, and adventure products should be promoted intensively so that Socotra will have a variety of products that can be experienced by potential tourists and will make Socotra distinguish itself from other competitive destinations.